Betel Quid Chewing Without Tobacco: A Meta-analysis of Carcinogenic and Precarcinogenic Effects. (March 2015) - Song, Han; Wan, Yi; Xu, Yong-Yong
Betel quid without tobacco is an important factor influencing the incidences of oral cancer and precancer. This study systematically evaluated the associations between betel quid containing no tobacco and oral cancer and precancer, with implications for the prevention of oral cancer. We searched MEDLINE, ISI Web of Science, and EMBASE (to April 2011) and retrieved studies that investigated the relationship between chewing betel quid and oral cancer (or precancer). We performed a meta-analysis to summarize the published data and describe the prevalence of betel quid use with regard to cancerous diseases. In all, 19 eligible studies that reported odds ratios and 95% confidence intervals for oral cancer with respect to betel quid were included. The analysis identified an association suggesting that betel quid might be an important risk factor for oral cancer and precancer. The results of this review suggest that betel-chewing-cessation programs should be developed to help prevent oral diseases.